Generalized Analysis of Gasifier Performance using Equilibrium Modeling - Ravikiran, Anapagaddi; Renganathan, Thiruvengadam; Pushpavanam, Subramaniam; Voolapalli, Ravi Kumar; Cho, Young Sang (AMER CHEMICAL SOC, 2012)
Thermodynamic modeling of gasification process provides a quick estimate of performance of the gasifier. Most of the earlier work on thermodynamic modeling is restricted to a particular feedstock gasification agent combination and hence the results cannot be generalized. In the present work, the equilibrium modeling based on Gibb's free energy minimization approach is used to analyze the performance of gasification of any fuel using oxygen or steam. The performance is analyzed at the carbon boundary point at which the cold gas efficiency is maximum. The gasification temperature, amount of gasification agent required, composition of syngas, and cold gas efficiency are predicted using Aspen Plus. The results are presented as contour plots on Van Krevelen coordinates (H/C vs O/C) and interpreted based on simplified gasification reactions. The performance for different feedstocks represented in Van Krevelen diagram is also analyzed. Finally, advantage of cogasification of feedstocks is highlighted.